The optimal concentration of intralesional triamcinolone acetonide for patchy alopecia areata: A systematic review and meta-analysis - Hsuan-An Su; Yu-Tsung Chen; Yu-Chia Chen (Wolters Kluwer Medknow Publications, 2022)
Background: Intralesional steroid treatment for alopecia areata (AA) has been developed for decades, yet the optimal concentration of triamcinolone acetonide (TrA) is not well-established. Objectives: This review aims to determine the optimal concentration of intralesional TrA in treating patchy AA. Methods: We conducted a systematic review and meta-analysis, and searched the Cochrane Library, Embase, and PubMed databases on July 4, 2021, to identify randomized or nonrandomized comparative studies reporting the response rates and/or adverse events among AA patients treated with various concentrations of TrA. The meta-analysis of proportions and odds ratios was analyzed using random-effects modeling. Results: Nineteen studies and a total of 783 participants were included. The estimated response rate of 5 mg/dl (74.82%, 95% confidence interval [CI] 64.99%-83.50%) was shown to be more efficacious than 2.5/3.33 mg/dl (38.64%, 95% CI 16.98%-62.99%) but similar to 10 mg/dl (71.06%, 95% CI 59.72%-81.20%), while pooled estimate of odds ratios revealed higher efficacy with 10 mg/dl than 5 mg/dl (odds ratio = 1.64, 95% CI 1.05-2.58, P = 0.031). The rates of skin atrophy were 18.05% (95% CI, 10.32%-27.38%), 11.49% (95% CI, 2.86%-24.84%), and 3.85% (95% CI, 1.27%-14.01%) in groups 10, 5, and 2.5/3.33 mg/dl, respectively. Higher concentration is associated with more skin atrophy in a dose-dependent fashion (P = 0.012). Heterogeneity among studies in the meta-analyses was high. Conclusion: The optimal intralesional concentration of TrA for patchy AA is probably 10 mg/dl with acceptable adverse events.